5G for construction: use cases and solutions - Mendoza, Jessica; De la Bandera Cascales, Isabel; Álvarez-Merino, Carlos Simón; Khatib, Emil Jatib; Alonso, Jesús; Casadelrrey-Díaz, S.; Barco-Moreno, Raquel (MDPI, 2021)
The world is currently undergoing a new industrial revolution characterized by the digitization and automation of industry through the use of Information and Communication Technologies (ICT). The construction sector is one of the largest sectors of industry. Most of the tasks associated with this sector are carried out in worksites that are defined by their dynamism, decentralization, temporality and by the intervention of a large number of workers, subcontractors, machinery, equipment and materials. These characteristics make this sector a great challenge for the implementation of ICT. In this paper, the benefits of the use of the Fifth Generation (5G) of mobile networks in the construction industry are presented. To that end, first the digitization and automation needs of the sector are jointly analyzed, establishing different use cases and identifying the requirements of each one. Then, the main characteristics of 5G that address these use cases are identified. Finally, a global framework for the application of 5G technology to construction industry is proposed.
Keywords: Telecomunicaciones; Industria de la construcción; 5G Networks; Industry 4.0; Use cases